Islamic Law in the Rule of Sadd Adz-Dzari'ah on the Transfer of Agricultural Land Function to Housing in Grobogan - M. Junaidi; Alifannisa Shella Hermininda (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
This research provides an in-depth exploration of Islamic legal aspects related to the conversion of agricultural land into residential areas, with a focus on the principle of Sadd Adz-Dzari'ah. This principle serves as the primary foundation for the research, playing a crucial role in regulating the land transformation process and establishing legal boundaries that must be adhered to. Through a case study conducted in the Grobogan Regency, this research aims to evaluate the application of the Sadd Adz-Dzari’ah principle in the context of agricultural land conversion. The research methodology employs a qualitative approach, utilizing in-depth interviews and document analysis. The collected data is analyzed using content analysis techniques to identify patterns and key themes related to the implementation of the Sadd Adz-Dzari’ah principle in land conversion. The main objectives of this study include gaining a profound understanding of the principle, evaluating its implementation in the conversion of agricultural land to residential areas in Grobogan Regency, analyzing the social, economic, and environmental impacts of the land-use changes, and presenting policy recommendations to enhance justice and sustainability, considering Islamic values. The research found that Islam with its sadd adz-dzariyat concept does not prohibit the conversion of agricultural land into housing as long as it provides maslahat for the community and is carried out based on existing statutory provisions and instead encourages the utilization of agricultural land for various purposes so that the land is not neglected and eventually dies without being utilized. Thus, this research is expected to significantly contribute to understanding the relevance and implementation of the Sadd Adz-Dzari’ah principle in the context of changing land use in rural communities. It also aims to provide a foundation for better policies aligned with Islamic values.